1985
DOI: 10.1212/wnl.35.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Perimesencephalic hemorrhage

Abstract: We studied 28 patients with subarachnoid hemorrhage and normal angiograms. On early CT (within 5 days) in 13 cases, blood was seen mainly or only in the cisterns around the midbrain. This pattern of hemorrhage was found in only 1 of 92 patients with a ruptured aneurysm. None of the unexplained perimesencephalic hemorrhages was associated with intracerebral hematoma or intraventricular hemorrhage. The clinical features also differed from those of aneurysmal hemorrhage; loss of consciousness was rare, and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
235
4
8

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(256 citation statements)
references
References 0 publications
9
235
4
8
Order By: Relevance
“…1,2 Since the systematic description by van Gijin et al, 3 perimesencephalic (pm)SAH and non-perimesencephalic (non-pm)SAH are commonly distinguished 1,2,4 In patients with pmSAH, the blood is located strictly around the midbrain and/or brainstem (Fig. 1A), while in patients with non-pmSAH the hemorrhage extends into adjacent cisterns (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since the systematic description by van Gijin et al, 3 perimesencephalic (pm)SAH and non-perimesencephalic (non-pm)SAH are commonly distinguished 1,2,4 In patients with pmSAH, the blood is located strictly around the midbrain and/or brainstem (Fig. 1A), while in patients with non-pmSAH the hemorrhage extends into adjacent cisterns (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 These patients often exhibit a pattern of hemorrhage on CT scans that is known as NAPH. This pattern was first described by van Gijn et al in 1985 2 as an SAH in which blood was limited primarily to the perimesencephalic cisterns with no evidence of aneurysm on angiography.…”
mentioning
confidence: 69%
“…Studies have shown that Ͼ90% of patients who present with the NAPH pattern have limited morbidity, and mortality is extremely rare. [2][3][4] These observed outcomes are in contrast to those of untreated aneurysmal SAH, in which morbidity and mortality rates are Ͼ50%.…”
mentioning
confidence: 93%
“…6) Generally, the clinical manifestation of PNSAH is sudden onset of headache, similar to that of aneurysmal SAH. 8) The natural history of PNSAH is benign, and PNSAH causing focal neurological deficit such as unilateral cranial nerve palsy is quite rare. Recently, the prevalence of anosmia was reported as one in 16 of patients with PNSAH.…”
Section: Introductionmentioning
confidence: 99%